(untitled) (Development Service Industry Management, 2025)
The aim of the article is to generalize the theoretical principles of financial and economic diagnostics of the enterprises functioning, in particular transport enterprises, in connection with their logistics activities in an unstable environment. Methodological problems of financial and economic diagnostics are highlighted: identification of the concept of "diagnostics" with the concept of "analysis", separation of the concepts of economic and financial diagnostics. It is substantiated that financial and economic diagnostics is a comprehensive process of assessing the financial and economic condition of an enterprise, aimed at identifying its stability, efficiency and risks, which includes the analysis of key financial indicators, such as liquidity, profitability, solvency, as well as the study of economic aspects, in particular competitiveness, development strategy and the influence of the external environment. A system of financial and economic diagnostics’ principles is developed. included the principles of systematicity, efficiency, adaptability of tools, realism of assessment, integration of qualitative and quantitative indicators, predictability, and continuity. The functions of the diagnostic system in an unstable environment (control and evaluation, prognostic, anti-crisis, integrative, navigation and adaptive) are determined. It is shown that the structure of a modern enterprise diagnostic system should include components that are responsible for performing specific functions aimed at ensuring effective analysis, forecasting and management of activities, that is, include an analytical module, an information and logistics module, a risk management module, a strategic and diagnostic interface module, and a monitoring and adaptation module. It is substantiated that diagnostics of the transport enterprise’s logistics activities involves assessing their functional state, adaptability, synchronization of subsystems, and ability to respond to market disturbances. A logistics activity diagnostics system has been developed, including indicators of transport logistics, warehouse logistics, inventory management and general logistics KPIs.